The genetic diversity of Plasmodium vivax populations. - Cui, L; Escalante, A; Imwong, M; Snounou, G (2003)
Little is known of the genetic diversity and population structure of Plasmodium vivax, a debilitating and highly prevalent malaria parasite of humans. This article reviews the known polymorphic genetic markers, summarizes current data on the population structure of this parasite and discusses future prospects for using knowledge of the genetic diversity to improve control measures.